2012
DOI: 10.1053/j.gastro.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Detection of Pancreatic Lesions in Asymptomatic High-Risk Individuals

Abstract: BACKGROUND & AIMS The risk of pancreatic cancer is increased in patients with a strong family history of pancreatic cancer or a predisposing germline mutation. Screening can detect curable, non-invasive pancreatic neoplasms, but the optimal imaging approach is not known. We determined the baseline prevalence and characteristics of pancreatic abnormalities using 3 imaging tests to screen asymptomatic, high-risk individuals (HRI). METHODS We screened 225 asymptomatic adult HRI at 5 academic US medical centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
471
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 593 publications
(515 citation statements)
references
References 34 publications
10
471
1
1
Order By: Relevance
“…CT, MRI, and EUS detected an abnormal pancreatic finding (pancreatic cysts or a dilated pancreatic duct) in 11%, 33.3%, and 43.6% of the high‐risk cases, respectively. Three cases with high‐grade dysplasia in IPMN or multiple intraepithelial neoplasms were finally diagnosed 52. A German study (FaPaCa) enrolled 76 high‐risk cases in a screening program using annual EUS, magnetic resonance cholangiopancreatography (MRCP), and laboratory tests for 5 years.…”
Section: Screening Programs For High‐risk Casesmentioning
confidence: 99%
“…CT, MRI, and EUS detected an abnormal pancreatic finding (pancreatic cysts or a dilated pancreatic duct) in 11%, 33.3%, and 43.6% of the high‐risk cases, respectively. Three cases with high‐grade dysplasia in IPMN or multiple intraepithelial neoplasms were finally diagnosed 52. A German study (FaPaCa) enrolled 76 high‐risk cases in a screening program using annual EUS, magnetic resonance cholangiopancreatography (MRCP), and laboratory tests for 5 years.…”
Section: Screening Programs For High‐risk Casesmentioning
confidence: 99%
“…These abnormal findings were proven or suspected neoplasms in 85 patients. Among these patients, three had high-grade dysplasia in IPMNs or multiple intraepithelial neoplasms [27]. These results suggested that screening of asymptomatic high-risk individuals for PC may frequently reveal small cystic lesions, including curable noninvasive neoplasms, and that EUS and MRI may be better than CT for the early diagnosis of pancreatic neoplasms [28].…”
Section: Screening Programs For High-risk Individualsmentioning
confidence: 92%
“…Most studies involved FPC families, while a few included carriers of a PDAC-associated gene defect [12,[14][15][16]. The screening protocols used in these studies varied widely, including MRI only, both MRI and endoscopic ultrasound (EUS), or MRI with optional EUS.…”
mentioning
confidence: 99%